2002
DOI: 10.3354/meps241201
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in otoliths indicate the use of open-coast versus bay nursery habitats by juvenile California halibut

Abstract: Many coastal fishes use inshore nursery habitats as juveniles, but it is often difficult to define which nursery areas supply most recruits to adult populations. We tested whether trace element concentrations in otoliths can be used to identify which of 2 nursery habitats (bays or shallow open coast) were occupied by juvenile California halibut. Juveniles from bays in 1998 had concentrations of Cu and Pb in their otoliths that were higher than those in open coast juveniles of the same year. This broad-scale di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 42 publications
5
64
0
Order By: Relevance
“…The majority of fish within embayments were in Mission and San Diego bays. Our findings concerning nursery habitat contribution show general agreement with the results of Forrester and Swearer (2002), who employed an elemental fingerprinting approach along a 300 km section of southern California to determine nursery habitat utilization. They concluded that approximately 50% of adult halibut had utilized protected embayments as nursery habitats, while the remaining 50% spent their juvenile period in the shallows of the exposed coastline.…”
Section: Distribution Of 0-group Fish Among Nursery Habitat Alternativessupporting
confidence: 80%
“…The majority of fish within embayments were in Mission and San Diego bays. Our findings concerning nursery habitat contribution show general agreement with the results of Forrester and Swearer (2002), who employed an elemental fingerprinting approach along a 300 km section of southern California to determine nursery habitat utilization. They concluded that approximately 50% of adult halibut had utilized protected embayments as nursery habitats, while the remaining 50% spent their juvenile period in the shallows of the exposed coastline.…”
Section: Distribution Of 0-group Fish Among Nursery Habitat Alternativessupporting
confidence: 80%
“…This is reflected in an increasing number of published papers that mostly deal with tropical regions and, to a lesser extent, with temperate regions (i.e. Forrester & Swearer 2002;Vasconcelos et al 2007Vasconcelos et al , 2008Standish et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…These elements are extremely sensitive to any changes in laser and ICP operating conditions (Koch and Günther, 2007) (Newman, 1996). In the analysis of otoliths of juvenile halibut by high resolution ICP-MS, for instance, instrumental results were sporadic for several trace elements, including Ag, Al, Cd, Co, Ni, Sn and Zn, due to the detection problems, therefore, these elements were not considered in statistical evaluations (Forrester and Swearer, 2002).…”
Section: Analytical Merits Of Preconcentration Icp-ms For Micromill Smentioning
confidence: 99%
“…In this study, we opted for a different tack on this problem and developed a probe-based method -high resolution micromill sampling -a method that mechanically isolates otolith's core corresponding to the first year of life. A solid phase preconcentration procedure was interfaced to an ICP-MS instrument to enhance the sensitivity since high variability and inaccuracy in instrumental results for trace elements were mainly due to the lack of sensitivity as was observed in the past studies (Milton and Chenery, 2001;Forrester and Swearer, 2002 …”
Section: Analytical Merits Of Preconcentration Icp-ms For Micromill Smentioning
confidence: 99%
See 1 more Smart Citation